The Concept of the Remote Devices Content Management - Miroslav Behan; Ondrej Krejcar (Journal of Computer Networks and Communications)
Modern mobile communication devices which are often used as remote access to information systems bring up many advantages for user. Unfortunately in some cases when user has several different mobile devices for the same remote access, a problem of multiplatform and multivendor environment fragments productivity by user knowledge in principals of approach to possible services, controlling or management of devices as well as features is available. The customizable interface of remote device management benefits by the control of all owned, authorized, or publically accessible devices from single point of user perspective. We propose a concept of such information system which takes into account mobile devices and their content. Concept is suitable not only for Apple iOS or Google Android, but also it covers all mobile platforms as well as the sensors capabilities of mobile devices which can turn such mobile Smart Device to Smart and mobile sensor concentrator.